A high-performance angular speed measurement method based on adaptive hysteresis switching techniques. (December 2015) - Huang, Haiming; Chou, Wusheng; Zhang, Zuojiang
Abstract: The high-performance measurement of angular speed (AS) is an essential requirement for achieving the high accuracy of machine control and monitoring. This paper proposes a new adaptive AS measurement system, which minimizes AS errors and fluctuations from conventional AS methods in a wide range of AS measurement. Unlike the conventional switches used previously, the system is composed of two layers of hysteresis switches, hereinafter referred to as the inner and outer hysteresis switch, respectively, to count pulses from an optical encoder adaptively. To highlight the key techniques used, the system is named as a hysteresis switch-based adaptation AS measurement (HS-AASM). The proposed method is designed and implemented based on a cost-effective TMS320F28335 digital signal controller (DSC). The performance analyses and experimental verifications show that the HS-AASM method outperforms the existing methods. Highlights: A new adaptive angular speed (AS) estimate method minimizes AS errors. Hysteresis switching technology is applied to avoid speed fluctuations. Errors caused by the mechanical errors of optical encoder are removed. Merits of high accuracy, fast response, and less fluctuation are achieved. Two-layer hysteresis switches system is realized in DSC.